TEACHERS’ PERCEPTION AND READINESS IN IMPLEMENTING THE MERDEKA BELAJAR CURRICULUM - Oristia Giovani P (Merwin Publisher, 2024)
The purpose of to find out the teachers’ perception of the Merdeka Curriculum, the teachers’ readiness for the Merdeka Curriculum, and the implementation of the perception & readiness of teachers about the Merdeka Curriculum of SMP Negeri 3 Binjai. The research methodology in this study is qualitative. The technique to determine the sample is purposive sampling with the total of respondents that allowed this research being ten teachers. The result of this study showed teachers at SMP 3 Binjai have a positive perception and negative perception. Positive perception of the Merdeka Belajar curriculum which is free to teach, students are free to express and develop according to their interests and talents and form students' character for the better. In contrast, a negative perception of the Merdeka Belajar curriculum is due to the implementation of an independent curriculum that prioritizes student character and ignores students' knowledge abilities. Even though students' knowledge skills are needed to continue to a higher level. In addition, the allocation of learning time is too short, and the learning time for the Pancasila profile and the P5 project is too long, resulting in lagging teaching materials, and learning resources such as cell phones that not all students can afford economically, some teachers are technologically challenged, the three teachers who feel comfortable with the old standards and have no experience in independent learning. Overall, teachers and schools are ready to implement the Merdeka curriculum.